k = 0 ∑ ⌊ 3 n − b ⌋ ( 3 k + b n )
Let n , b ∈ Z , where n ≥ 1 and 0 ≤ b < 3 . Find the closed form of the sum above.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sir Alan ,i like your solution and here is my idea (the core of my solution should be the same as yours).
Notation : let S r ( r = 0 , 1 , 2 ) stands for the asking sum when b=0,1,2 respectively.And w = c o s ( 3 2 π ) + i s i n ( 3 2 π ) .
In the expansion ( 1 + x ) n = k = 0 ∑ n ( k n ) x k , take x = 1 , w , w 2 respectively,we get
S 0 + S 1 + S 2 = 2 n S 0 + w S 1 + w 2 S 2 = ( 1 + w ) n S 0 + w 2 S 1 + w S 2 = ( 1 + w 2 ) n
Solve these linear equations,and the result is S r = 3 2 n + 3 2 c o s 3 ( n − 2 r ) π , r = 0 , 1 , 2 ,en,as desired.
This is absolutely superb. I never had the intuition to use complex algebra (I just tested which one worked for a few values). I am new to a lot of this complex algebra, so seeing it in application with binomial theorem and understanding said applications really boosts my confidence and makes me understand the theory more so. This solution was hence both beautiful and very helpful.
Problem Loading...
Note Loading...
Set Loading...
Let S be the desired sum and let w = e 2 π i / 3 . Consider the following sum: m = 0 ∑ 2 w − b m ( 1 + w m ) n = m = 0 ∑ 2 w − b m k = 0 ∑ n w m k ( k n ) = m = 0 ∑ 2 k = 0 ∑ n w m ( k − b ) ( k n ) = k = 0 ∑ n m = 0 ∑ 2 w m ( k − b ) ( k n ) When k − b is a multiple of 3 we have m = 0 ∑ 2 w m ( k − b ) = 3 , otherwise we have m = 0 ∑ 2 w m ( k − b ) = 0 , so we are left only with the terms of the sum where k ≡ b ( m o d 3 ) , so: m = 0 ∑ 2 w − b m ( 1 + w m ) n = k = 0 ∑ ⌊ 3 n − b ⌋ 3 ( 3 k + b n ) = 3 S Finally, using the fact that w 2 + w + 1 = 0 , S = 3 1 m = 0 ∑ 2 w − b m ( 1 + w m ) n = 3 1 [ ( 1 + 1 ) n + w − b ( 1 + w ) n + w − 2 b ( 1 + w 2 ) n ] = 3 1 [ 2 n + w − b ( − w 2 ) n + w − 2 b ( − w ) n ] = 3 1 [ 2 n + ( − 1 ) n ( w 2 n − b + w n − 2 b ) ] = 3 1 [ 2 n + ( − 1 ) n ( w − ( n + b ) + w n + b ) ] = 3 1 [ 2 n + 2 ( − 1 ) n cos ( 3 2 π ( n + b ) ) ]